Raman spectroscopic study of photosensitive damage to lysozyme structure sensitized by hypocrellin A. Issue 5 (2006) - Zhou Zhou, J. H. J. H.; Wu Wu, X. H. X. H.; Wei Wei, S. H. S. H.; Gu Gu, X. T. X. T.; Feng Feng, Y. Y. Y. Y.; Wang Wang, X. S. X. S.; Zhang Zhang, B. W. B. W.
Abstract : Laser Raman spectroscopy was used to detect the nature of the structural change in lysozyme sensitized by hypocrellin A (HA) at the molecular level. The results indicated that the orderly structure of lysozyme has been damaged by the active oxygen ( 1 O2, O2 −· and. OH, etc.) generated by HA, and cause the changes in H-bonds system of the main chain and the side chain of lysozyme.